Effect of Advance Organizer’s Strategy on Academic Performance in Teaching Basic Science among Junior Secondary School Students in Bauchi Metropolis - Auwal, Rabiu; Hassan, M. Gambo; Musa, Saliha Abubakar (Kashere Journal of Education, 2025)
The study investigated the effect of an advanced organiser's instructional strategy on academic performance when teaching basic science to junior secondary school students in Bauchi Metropolis. Two research objectives were stated: to determine the difference in students' mean performance scores between pre-test and post-test mean scores of students in the experimental group and to examine the difference in the students' post-test mean scores of students taught using the advance organiser's instructional strategy and those taught using the conventional method. Two research questions were stated: "What is the difference in the students' mean performance scores between pre-test and post-test mean scores of students in the experimental group?" And what is the difference in the students’ performance mean scores between students taught using the advanced organiser's instructional strategy and those taught using the conventional method?" "Two research hypotheses were created, a quasi-experimental research design was used, a total of 4,448 students were identified for the 2024/2025 academic year, and a simple random sampling method was applied to select the school, with one complete class chosen by drawing lots." An intact class of one hundred and nineteen students was found, sixty-seven (67) in the experimental group and fifty-two (52) students in the control group. The mean and standard deviation were used to answer the research questions, while an independent sample t-test was used to analyse the hypotheses. The results showed that the paired samples t-test found a significant difference between the average scores of students in the experimental group before and after the test at the 0.05 level of significance; the average score after the test (????̄ = 67.00) was much higher than the average score before the test (????̄ = 42.00), showing an increase of 25.00. This result suggests that the Advance Organiser Strategy had a significant positive effect on students’ academic performance in Basic Science. The study recommends incorporating advanced organisers into teaching practices, providing equal opportunities for all students, conducting further research, developing inclusive learning materials, and providing professional development for educators. The findings have implications for teaching practices and educational policy, highlighting the need for further research into the application of advance organizers in various educational contexts